Caracterización de algunos minerales asbestiformes de uso industrial - Lescano, Leticia (2010)
A mineralogical and morphologic characterization of some asbestiformes minerals of common use in the industry was made. Natural samples of chrysotile, lizardite and antigorite of the serpentine group; and actinolite, tremolite and anthophyllite of the amphiboles group were used. They were studied with optical microscope on with the immersion method, scanning electron microscopy - EDS and X-ray diffraction. The resolve of the morphology and size of fibers has special interest by the implications that this has in the human health. These characteristics determine the penetration of asbestos fibers in the respiratory routes, those that are accumulated in the lungs, having been able to cause to cancer or asbestosis.